Repetitive transcranial magnetic stimulation can improve the fixation of eyes rather than the fixation preference in children with autism spectrum disorder - Tian, Li; Ma, Shuai; Li, Yin; Zhao, Meng-fei; Xu, Chang; Wang, Chen; Zhang, Xin; Gao, Lei (Frontiers in Neuroscience, 2023)
Background Transcranial magnetic stimulation (TMS) has been introduced into the intervention of autism spectrum disorders (ASD) as a possible new therapeutic option for modifying pathological neuroplasticity. However, the stimulating protocols of rTMS for ASD have not been approved unanimously, which affects the clinical popularization and application of rTMS. In addition, there is little research on the improvement of social processing of autistic children by rTMS. Methods We explored the clinical efficacy of rTMS and improvement of face processing with the protocol of left high-frequency and right low-frequency on bilateral dorsolateral prefrontal cortex (DLPFC), with a sample of 45 ASD participants aged 2–18. Results Our results showed that both the score on the Childhood Autism Rating Scale (CARS) and the fixations on the eyes of the human faces improved by two-session rTMS intervention, except for the percentage of eyes fixation. The mediation analysis indicated the item of “Adaptation to Change” of CARS mediated dominantly the improvement of eye-gaze behavior of ASD participants by rTMS. Conclusion Our study revealed the mechanism of rTMS in improving the eye-gaze behavior of the autism population, deepened the understanding of the function of rTMS in treating autistic social disorders, and provided a reference for combined treatment for ASD.